K Value: An Indicator that can Characterize the Cold and Hot Properties of Traditional Chinese Medicines - Yang, Meina; Pang, Jingxiang; Zhang, Zhongwen; Fu, Jialei; Fan, Hua; Zhang, Yufeng; Min, Lingyuan; Zhou, Baochen; Han, Jinxiang (Frontiers in Pharmacology, 2022)
Aims: The cold and hot properties of Chinese medicines are an important concept to represent the function of drugs, and are also a unique classification method of traditional Chinese medicine(TCM). The method reflects an herb's therapeutic properties and guides reasonable clinical prescription. However, the present key problem is the lack of an objective and quantitative evaluation index for the cold and hot properties of Chinese herbs.Delayed luminescence (DL) is the long-term afterglow of biological systems after illumination with light, which can reflect differences in herbal materials prepared under different conditions.We aim to use S. obliquus as an indicator organism to characterize the differences between the cold and hot properties of Chinese herbs. Methods: Scenedesmus obliquus(S. obliquus) was used as an indicator organism to characterize the differences between the cold and hot properties of Chinese herbs. The decoction solution of different properties of Chinese herbs was added to S. obliquus culture medium; then, the delayed luminescence (DL) of S. obliquus after the addition of decoctions of different properties of Chinese herbs was measured to obtain information on the effect of different properties of Chinese herbs on S. obliquus. Many DL parameters were calculated, and ROC curve analysis was applied with the aim of finding a suitable parameter that can characterize the differences in cold and hot properties of Chinese herbs. Results: Our results show that the K value is a sensitive parameter that can reflect the differences of cold and hot properties of Chinese herbs, thus providing new insights into the cold and hot properties of Chinese herbs. Conclusions: DL measurement of S. obliquus after addition of different properties of Chinese herbs could be a novel and promising method to study the cold and hot properties of Chinese herbs.